Pharmacokinetics-Based Chronoefficacy of Semen Strychni and Tripterygium Glycoside Tablet Against Rheumatoid Arthritis - Jingpan Lin; Jingpan Lin; Lu Gao; Lu Gao; Yanke Lin; Yanke Lin; Shuai Wang; Shuai Wang; Zemin Yang; Zemin Yang; Shujing Ren; Shujing Ren; et al. (Frontiers Media S.A., 2021)
Rheumatoid arthritis is a systemic autoimmune disease characterized by synovial inflammation and bone destruction. Identifying drugs with time-varying efficacy and toxicity, and elucidating the mechanisms would help to improve treatment efficacy and reduce adverse effects. Here, we aimed to determine the chronoefficacy of semen strychni (SS) and tripterygium glycoside tablet (TGT) against rheumatoid arthritis in mice, and to investigate a potential role of circadian pharmacokinetics in generating chronoefficacy. SS extract and TGT suspension were prepared with ultrasonication. Effects of SS and TGT on collagen-induced arthritis (CIA) were evaluated by measuring TNF-α and IL-6 levels. SS dosed at ZT18 was more effective in protecting against CIA than drug dosed at ZT6 (i.e., lower levels of key inflammatory factors at ZT18 than at ZT6). This was accompanied by higher systemic exposure levels of strychnine and brucine (two main putative active ingredients of SS) in ZT18-treated than in ZT6-treated CIA mice. TGT dosing at ZT2 showed a better efficacy against CIA as compared to herb doing at ZT14. Consistently, ZT2 dosing generated a higher exposure of triptolide (a main putative active ingredient of TGT) as compared to ZT14 dosing in CIA mice. Moreover, strychnine, brucine, and triptolide significantly inhibited the proliferation of fibroblast-like synoviocytes, and reduced the production of TNF-α and IL-6 and the mRNAs of TNF-α, IL-6, COX-2, and iNOS, suggesting that they possessed an anti-arthritis activity. In conclusion, SS and TGT display chronoefficacy against rheumatoid arthritis in mice, that is attributed to circadian pharmacokinetics of main active ingredients. Our findings have implications for improving treatment outcomes of SS and TGT via timed delivery.